The effect of moisture and air gap on the thermal protective performance of fabric assemblies used by wildland firefighters. Issue 8 (2nd August 2016) - He, Hualing; Yu, Zhi-Cai; Song, Guowen
Abstract : The thermal protection performance (TPP) provided by fabric assemblies used by wildland firefighters is greatly affected by both the moisture and the air gap trapped in multilayer fabrics. In this paper, the effect of moisture, coupled with air gap on TPP was analyzed under radiant heat exposures of 21 kW/m 2 . The air gap sizes from 0 to 5.2 mm were analyzed using an air gap height regulation device; the moisture content of the multilayer fabric combinations around 0–70% were obtained by spraying distilled water to simulate varying amounts of sweat absorption. The results obtained indicate that certain air gaps entrapped in multilayer fabric system have a positive effect on TPP for both dry and wet multilayer fabric combinations. However, obvious trend changes in thermal protection were observed among dry and wet configurations when the air gap was moved to different positions. For the wet configurations, the second-degree burn time increased as the air gap moved further from the heat source, which was contrary to burn time response under dry conditions. These findings suggest that the complicated reciprocal effect of air gap and moisture on thermal protection should be both considered in analyzing the TPP of fabric assemblies.